Soil biotic and abiotic traits as driven factors for site quality of Araucaria angustifolia plantations - Souza T.* (2022)
© 2021, Plant Science and Biodiversity Centre, Slovak Academy of Sciences.The role of soil biotic and abiotic factors in crucial soil functions such as primary production, organic matter dynamics, nutrient cycling, and soil biota community structure in the Araucaria ecosystem remains poorly quantified. We aimed to understand how the development of organic horizons, root growth, soil chemical properties, and the entire soil biota community affected the soil quality in even aged and monospecific Araucaria angustifolia plantations. We collected soil monoliths to describe layers of organic matter and the complex soil food web into these layers. We determined soil pH, soil moisture, total nitrogen, available P, and total organic carbon into each layer (litter, F-layer, H-layer, and A horizon), the biomass of fine roots, the community structure of soil biota, arbuscular mycorrhizal fungi, and nematodes, as well as the microbial biomass carbon. In the high-quality site, there was significantly higher organic matter formation, nutrient cycling (N and P), root growth, soil moisture, soil biota diversity, arbuscular mycorrhizal fungi, and nematodes evaluated by the microbial biomass carbon compared to the low-quality site. High-quality sites promote the development of organic horizons, root growth on superficial layers that provide plant nutrient release, the A horizon nutrient contents, and the entire soil biota community in monospecific Araucaria angustifolia plantations located on humid subtropical Cambisols. This creates a positive plant-soil feedback that maintains soil quality and increases primary production, nutrient cycling, and habitat and food for the soil food web.